Dynamic Optimization of Inventory: A Comprehensive Model Incorporating Price-Sensitive Stochastic Demand, Promotional Strategies, Rework, Preservation Technology, and Carbon Emission Reduction - M. Palanivel; M. Venkadesh; S. Vetriselvi; R. Sundararajan (Discrete Dynamics in Nature and Society)
This paper presents an inventory model with a price-dependent stochastic demand and finite replenishment rate mode. It establishes a production-inventory system with a controllable deterioration rate, preservation technology, different types of rework process, promotional effort, and carbon emission reduction. This study finds the optimal solution and determines the most efficient production and safety technology investments to maximize the manufacturer’s total profit over the planning horizon. Also, this inventory model balances sustainability and profitability to maximize the profit and to determine the optimal cycle length. In addition, the research highlights the most advantageous investments in production and preservation technology, emphasizing their critical role in increasing profitability and identifying the most effective duration of the production cycle. The study presents a comprehensive approach to inventory optimization that tackles practical and strategic challenges in manufacturing contexts. This research refers to cases and numerical examples, providing management insights and sensitivity analysis to determine the optimal course of action to change the parameters of the model.